Construire et utiliser son réseau en Aquitaine 1362-1380 : instrumentalisation de la justice et intérêts géopolitiques - Élodie Giard (Criminocorpus)
The alternation of power in Aquitaine from 1360 to 1372 led the various actors who succeeded one another to adapt their policies in a context where the question of loyalty became a central element in the lasting establishment of authority. No aristocratic family was entirely partisan of one or the other dominant. There is division, and many families experience internal conflicts. Justice is then used by aristocratic families, sometimes even to serve opposing interests within the same lineage. These individuals mobilised their network, made up of vassals but also members of other families who had made the same political choices, both in the English and French camps.